Damage Function and Its Application - Tarantsev Andrey (EDP Sciences, 2021)
The types of damage functions for objects in the event of various emergency situations - fires, accidents, emergencies, etc. - are considered. The methods of constructing damage functions using expert methods and taking into account the actions of emergency services to eliminate emergency situations and their consequences are presented. The possibility of comparing the effectiveness of various methods of emergency response using the damage function is shown. An example of assessing damage reduction while increasing the efficiency of fire extinguishing by automatic installations is provided.